Vertical Addressing of 1‐Plane Electrodes for Digital Microfluidics. Issue 7 (16th December 2021) - von der Ecken, Sebastian; Sklavounos, Alexandros A.; Wheeler, Aaron R.
Abstract: Digital microfluidics (DMF) has become a mainstay in the microfluidics and microelectromechanical communities. Many users rely on simple DMF devices featuring a small number of rows and columns of electrodes that can be rapidly manufactured using "one plane" lithographic or printing techniques. But as the popularity of DMF grows, there are increasing needs for larger devices that can facilitate multiplexed handling of many samples and reagents in parallel. One option for scaling DMF devices is to use "vertical addressing" techniques such as printed circuit boards (PCBs), but PCBs formed using standard techniques exhibit topography that is not ideal for smooth and reliable droplet movement. A new method to produce DMF devices using vertical addressing of 1‐plane electrodes (VAPE‐DMF) is introduced. This method, which separates devices into "covers" (bearing 1‐plane electrodes) and "sub‐substrates" (for vertical addressing), enables rapid and inexpensive manufacture of devices with arbitrarily large driving electrode arrays. This work describes how to manufacture VAPE‐DMF devices and demonstrates a proof‐of‐concept device with an array of 336 electrodes to handle 48 droplets to run 24 reactions in parallel. It is proposed that VAPE‐DMF represents a useful new development for the growing community of users and innovators of digital microfluidics and related methods. Abstract : This work introduces a new method for forming and using digital microfluidic devices: Vertical addressing of 1‐plane electrodes (VAPE‐DMF). The new technique combines the advantages of standardized printed circuit board manufacturing with the facility of droplet movement on surfaces that do not suffer from unwanted topography.